Решение задачи выбора маршрутов с применением многокритериального подхода - Безрук, В. М.; Варич, В. В. (ХНУРЭ, 2011)
Abstract - Practical features of multi-criteria approach to solving the problem of optimal routing in a multiservice network considered. To solve this problem in the theory of decisionmaking using multi-criteria approach - a selection of some properties of objects (features), them evaluation and decision on the results of the comparisons. Network model is chosen. The network form is MNV graph. It contain a set of nodes and links. We found a subset of the Paretooptimal routing options based set of indicators of quality.
Keywords: управление трафиком; управление мультисервисной сетью; телекоммуникационная сеть